Phenolic anticorrosive paint with high flash point as well as preparation method and application of phenolic anticorrosive paint
By combining xylene ol resin with hyperbranched polyester modified phenolic resin in phenolic resin coatings, and combining modified glass fiber and light stabilizer-β-cyclodextrin inclusions, the problems of low flash point and poor weather resistance of existing phenolic resin coatings are solved, and the performance improvements of high adhesion, flexibility and salt spray resistance are achieved.
Patent Information
- Application Number
- CN202510028046.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing phenolic resin coatings have low flash point, low safety, high VOC content and poor weather resistance, especially in outdoor beaches, which show poor salt spray resistance and humidity resistance.
Xylene ol resin is used to combine with hyperbranched polyester modified phenolic resin, and the adhesion, flexibility, salt spray resistance and moisture and heat resistance of the coating are improved by the use of modified glass fiber and light stabilizer-β-cyclodextrin inclusions.
It significantly improves the adhesion, flexibility, salt spray resistance and humidity and heat resistance of the coating, and is suitable for the protection of outdoor equipment/facilities at the beach, with improved flash point and enhanced safety.
Smart Images

Figure BDA0005233341640000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a high-flash-point phenolic anticorrosive coating and a preparation method and application thereof. Background Art
[0002] Phenolic resin coatings are widely used in wood, furniture, construction, machinery, motors, ships and chemical anti-corrosion coatings due to the advantages of their coating films such as high hardness, chemical corrosion resistance and insulation.
[0003] Traditional phenolic resin coatings use phenolic resin as the main film-forming substance, with 200# solvent oil, pigments, fillers, and drying agents as the main components. They have the following problems: (1) Due to the presence of solvent oil, the flash point of phenolic resin coatings is low and their safety is low; (2) During construction, a large amount of organic solvents are required for dilution, resulting in a high VOC content; (3) The weather resistance is poor.
[0004] To solve the above problems, a Chinese patent with publication number CN113861795A discloses an environmentally friendly high flash point phenolic anticorrosive coating and its preparation process, comprising the following steps: S1: preparing modified phenolic resin, modified alkyd resin, and composite drier; S2: uniformly mixing modified phenolic resin, modified alkyd resin, high flash point solvent, composite drier, melamine pyrophosphate, pigment, and additives, reacting for 30-45 minutes, grinding for 30-45 minutes, filtering, adding silicone acrylic emulsion, and mixing uniformly to obtain an anticorrosive coating. The coating prepared by this process has low VOC content, UV resistance, mechanical properties, corrosion resistance, water resistance, and flame retardancy, and is environmentally friendly and non-toxic. However, after long-term testing, the salt spray resistance and weather resistance of this technical solution are poor.
[0005] The Chinese patent with publication number CN112980230A discloses an anticorrosive coating with modified phenolic resin added, which includes modified phenolic resin and anticorrosive coating, wherein the modified phenolic resin is made of 4-tert-butyl phenol, paraformaldehyde, pentaerythritol, glycerol, rosin, catalyst A, catalyst B, antioxidant and high-purity nitrogen, and the amount of rosin, glycerol, pentaerythritol and catalyst is 100:5.5:7:0.1 in mass ratio, and the amount of 4-tert-butyl phenol, paraformaldehyde and catalyst is 100:30:0.1 in mass ratio. This technical solution introduces rosin ester into the phenolic resin system to form a copolymer, and the secondary copolymerization product is added to the anticorrosive coating system with epoxy ester as the main body, which can improve the drying speed, water resistance and adhesion of the anticorrosive coating. However, the actual drying time of this technical solution reaches 5 days, which may lead to the risk of lifting and biting the bottom during construction. Summary of the invention
[0006] In view of the above problems, the present invention provides a phenolic anti-corrosion coating with a high flash point, a preparation method and an application thereof. The coating obtained by the phenolic anti-corrosion coating provided by the present invention has good adhesion, flexibility, long-term salt spray resistance, weather resistance and moisture and heat resistance.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The first aspect of the present invention provides a high-flash point phenolic anti-corrosion coating, which comprises, by weight, 40-70 parts of xylene phenolic resin, 30-60 parts of hyperbranched polyester modified phenolic resin, 10-15 parts of silicone acrylic emulsion, 5-10 parts of modified glass fiber, 5-10 parts of pigment, 3-8 parts of solvent, 3-8 parts of light stabilizer-β-cyclodextrin inclusion complex, and 1-3 parts of drying agent.
[0009] Preferably, the xylene phenolic resin is composed of raw materials, by mass, of 20 parts of first formaldehyde, 10 parts of sulfuric acid, 25 parts of xylene, 10 parts of phenol, 0.1 parts of hydrochloric acid, 1 part of sodium hydroxide, 12 parts of second formaldehyde, and 20 parts of ethanol.
[0010] Preferably, the preparation method of the xylene phenolic resin is as follows: first, formaldehyde and sulfuric acid are uniformly mixed;
[0011] Add xylene, react at 70°C for 8h, let stand for 15min, remove the lower layer solution, wash with water until neutral, evacuate the product until no more effluent, cool to 25°C, add phenol, and when the temperature reaches 40°C,
[0012] Add hydrochloric acid, heat to 93°C, react for 15 minutes, react at 95°C for 20 minutes, quickly cool to 40°C, add sodium hydroxide, react for 10 minutes, add the second formaldehyde, heat to 90°C, react for 35 minutes, dehydrate at 75°C, cool to 60°C, add ethanol to adjust the solid content to 80%, and obtain xylene phenol-formaldehyde resin.
[0013] The preparation method of the hyperbranched polyester modified phenolic resin comprises the following steps: uniformly mixing formaldehyde, phenol, terminal hydroxyl hyperbranched polyester and water, adding sodium hydroxide for a first reaction to obtain an intermediate; adding nano titanium dioxide to the intermediate for a second reaction, dehydrating after the reaction, adding ethanol and mixing uniformly to obtain the hyperbranched polyester modified phenolic resin.
[0014] The inventors' previous research used xylene phenolic resin and modified alkyd resin for compounding. However, after long-term tests, it was found that the salt spray resistance and weather resistance of this technical solution were poor, and it was not suitable for the protection of outdoor equipment / facilities at the seaside. In order to solve this technical problem, the inventors creatively prepared a hyperbranched polyester modified phenolic resin, and compounded the hyperbranched polyester modified phenolic resin with xylene phenolic resin for use, which not only improved the adhesion and flexibility of the coating, but also improved its salt spray resistance and weather resistance. It is speculated that this is because the phenolic resin is first modified by a terminal hydroxyl hyperbranched polyester, and the terminal hydroxyl hyperbranched polyester contains a large number of terminal hydroxyl groups, which can participate in the reaction of formaldehyde and phenol. The invention relates to a method for modifying the phenolic resin by using nano-titanium dioxide. The nano-titanium dioxide reacts with the hydroxyl groups on the phenolic resin to form ether bonds, which can not only further improve the flexibility of the coating, but also improve the continuity and density of the coating, and can also form a passivation protective layer on the surface of the substrate to prevent the substrate from contacting with the outside world. Therefore, the obtained coating has excellent salt spray resistance and weather resistance.
[0015] Preferably, the terminal hydroxyl hyperbranched polyester is an aliphatic hyperbranched polyester, specifically sourced from Wuhan Hyperbranched Resin Technology Co., Ltd., model: H102.
[0016] Preferably, the mass ratio of the formaldehyde, phenol, terminal hydroxyl hyperbranched polyester and water is (0.4-0.5):1:(0.05-0.15):(2-4), preferably 0.45:1:0.1:3.1.
[0017] Preferably, the mass ratio of sodium hydroxide to phenol is (2-4):100.
[0018] Preferably, the temperature of the first reaction is 80-90° C., and the time of the first reaction is 2-4 h.
[0019] Preferably, the mass ratio of the intermediate to nano-titanium dioxide is 1:(0.1-0.3).
[0020] Preferably, the nano titanium dioxide is anatase nano titanium dioxide with a particle size of 10-30 nm, preferably 20 nm.
[0021] Preferably, the temperature of the second reaction is 60-80° C., and the time of the second reaction is 4-8 hours.
[0022] Preferably, the ethanol is added in an amount such that the solid content of the hyperbranched polyester modified phenolic resin is 70-80%.
[0023] Preferably, the solid content of the silicone acrylic emulsion is 48±1 wt %, specifically from Jiangsu Shengda New Material Technology Co., Ltd., model: SD-5281 nano silicone acrylic emulsion.
[0024] Preferably, the preparation method of the modified glass fiber comprises the following steps: uniformly mixing carboxylated glass fiber, amino hexagonal boron nitride, epichlorohydrin and water, and performing a hydrothermal reaction, and filtering, washing and drying the reaction product in sequence after the hydrothermal reaction to obtain an intermediate product; dispersing the intermediate product in an ethanol aqueous solution, adding tetraethyl orthosilicate and ammonia water to perform a stirring reaction, and filtering, washing and drying the reaction product in sequence after the stirring reaction to obtain a modified glass fiber.
[0025] Outdoor equipment / facilities at the seaside are in an environment of high temperature and high humidity, and the air contains a high salt content, which will cause serious corrosion and damage to the equipment / facilities. Therefore, it is very important to evaluate the moisture and heat resistance of phenolic anti-corrosion coatings. The inventors found that the moisture and heat resistance of phenolic anti-corrosion coatings prepared by compounding only xylene phenolic resin and hyperbranched polyester modified phenolic resin is poor. In order to solve the above technical problems, the inventors creatively prepared modified glass fibers. First, the carboxyl groups in the carboxylated glass fibers reacted with the amino groups in the amino hexagonal boron nitride, and the amino hexagonal boron nitride was grafted on the surface of the glass fibers. Then, silicon dioxide was loaded on the surface of the glass fibers. Through the above technical scheme, the continuity and density of the coating are further improved by utilizing the combined effect of the glass fibers, hexagonal boron nitride and silicon dioxide. In addition, the modified glass fibers can form hydrogen bond interactions with the phenolic acid resin modified by the terminal hydroxyl hyperbranched polyester, which is conducive to forming a staggered structure while improving the dispersibility of the modified glass fibers. Therefore, the moisture and heat resistance of the coating is improved, and the salt spray resistance and flexibility are also improved.
[0026] However, during the experiment, the inventors found that the moisture and heat resistance, flexibility and salt spray resistance of the glass fiber modified by mixed acid were poor, while the moisture and heat resistance, salt spray resistance and flexibility of the coating were excellent when the glass fiber was carboxylated by 3-[3-carboxyallylamide]propyltriethoxysilane. It is speculated that this is because 3-[3-carboxyallylamide]propyltriethoxysilane can introduce carboxyl groups and organic chains on the surface of the glass fiber at the same time, and the organic chain can improve the dispersibility of the glass fiber in the system and is conducive to the formation of a staggered structure, thereby improving the flexibility, salt spray resistance and moisture and heat resistance of the coating.
[0027] Further preferably, the preparation method of the modified glass fiber comprises the following steps: uniformly mixing carboxylated glass fiber, amino hexagonal boron nitride, epichlorohydrin and water, conducting a hydrothermal reaction at 100-110°C for 2-4 hours, and filtering, washing and drying the reaction product in sequence after the hydrothermal reaction to obtain an intermediate product; dispersing the intermediate product in an ethanol aqueous solution, adding tetraethyl orthosilicate and ammonia water, and stirring the reaction at 25-30°C for 2-3 hours, and filtering, washing and drying the reaction product in sequence after the stirring reaction to obtain a modified glass fiber.
[0028] Preferably, the mass ratio of the carboxylated glass fiber, amino hexagonal boron nitride, epichlorohydrin and water is 1:(0.5-0.8):(0.3-0.5):(40-60), preferably 1:0.7:0.4:50.
[0029] Preferably, the mass ratio of the intermediate product, ethanol aqueous solution, tetraethyl orthosilicate and ammonia water is 1:(30-40):(0.7-0.9):(0.9-1.1), preferably 1:25:0.8:1.
[0030] Preferably, the concentration of the ethanol aqueous solution is 60-80wt%.
[0031] Preferably, the preparation method of the carboxylated glass fiber is: glass fiber, 3-[3-carboxyallylamide]propyltriethoxysilane and ethanol are mixed, and stirred for reaction, and after the stirring reaction is completed, the product is filtered, washed and dried to obtain the carboxylated glass fiber.
[0032] Further preferably, the preparation method of the carboxylated glass fiber is: glass fiber, 3-[3-carboxyallylamide]propyltriethoxysilane and ethanol are mixed, and stirred for reaction at 25-30°C for 4-6 hours. After the stirring reaction is completed, the product is filtered, washed and dried to obtain the carboxylated glass fiber.
[0033] The glass fiber described in the present invention is glass fiber powder, which is obtained by grinding glass fiber.
[0034] Preferably, the mass ratio of the glass fiber, 3-[3-carboxyallylamide]propyltriethoxysilane and ethanol is 1:(0.4-0.6):(10-15), preferably 1:0.5:12.
[0035] Preferably, the preparation method of the amino-modified hexagonal boron nitride is: dispersing hexagonal boron nitride in water, adding polyethyleneimine and epichlorohydrin, stirring and reacting, and filtering, washing and drying the reaction product after the stirring reaction to obtain amino-modified hexagonal boron nitride.
[0036] The hexagonal boron nitride in the present invention is in powder form.
[0037] Further preferably, the preparation method of the amino-modified hexagonal boron nitride is: dispersing hexagonal boron nitride in water, adding polyethyleneimine and epichlorohydrin, stirring and reacting at 70-80°C for 2-4h, and filtering, washing and drying the reaction product after the stirring reaction to obtain amino-modified hexagonal boron nitride.
[0038] Preferably, the mass ratio of hexagonal boron nitride, water, polyethyleneimine and epichlorohydrin is (1-2): (25-50): (0.5-1): (0.5-0.9), preferably 1.5:40:1:0.8.
[0039] Preferably, the pigment is selected from at least one of titanium dioxide, red iron oxide, chrome yellow, phthalocyanine green, phthalocyanine blue and carbon black.
[0040] Preferably, the solvent is selected from at least one of dipropylene glycol methyl ether, ethylene glycol diacetate, cyclohexanone and carbon tetrachloride.
[0041] Preferably, the method for preparing the light stabilizer-β-cyclodextrin inclusion complex comprises the following steps:
[0042] S1, mixing carboxymethyl-β-cyclodextrin aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt, and N-hydroxysuccinimide evenly, and letting stand to obtain an activated carboxymethyl-β-cyclodextrin aqueous solution;
[0043] S2, mixing the activated carboxymethyl-β-cyclodextrin aqueous solution and the aminated hollow glass microspheres, and performing an amidation reaction. After the amidation reaction, centrifuging, filtering, and drying the product to obtain β-cyclodextrin loaded with hollow glass microspheres;
[0044] S3, mixing the light stabilizer and methanol to obtain a light stabilizer solution;
[0045] S4, mixing the β-cyclodextrin loaded with hollow glass microspheres, the light stabilizer solution and water, and stirring the mixture for reaction. After the stirring reaction, centrifuging, filtering and drying the product to obtain a light stabilizer-β-cyclodextrin inclusion complex.
[0046] In addition to direct sunlight, the refractive index of the sea surface to ultraviolet rays makes the ultraviolet rays at the seaside much higher than those in other places. Therefore, in order to further improve the weather resistance of phenolic anticorrosive coatings, the inventors creatively prepared a light stabilizer-β-cyclodextrin inclusion complex and unexpectedly found that the carboxymethyl-β-cyclodextrin was first modified with aminated hollow glass microspheres and then the light stabilizer was included. This not only improved the weather resistance of the coating, but also further improved the moisture and heat resistance and salt spray resistance of the coating. When the aminated hollow glass microspheres were replaced with aminated hexagonal nitrogen When boron is added, the above effect cannot be achieved. It is speculated that this is because the hollow glass microspheres have a hollow structure inside and have a low thermal conductivity, which can isolate the external heat from being transferred to the coating to a certain extent, thereby improving the moisture and heat resistance of the coating. At the same time, the hollow structure inside the hollow glass microspheres and the space barrier effect formed are conducive to improving the inclusion effect of carboxymethyl-β-cyclodextrin on the light stabilizer, thereby improving the weather resistance of the coating; in addition, the hollow glass microspheres further form a staggered structure in the system, thereby improving the salt spray resistance and moisture and heat resistance of the coating.
[0047] Preferably, the concentration of carboxymethyl-β-cyclodextrin in the carboxymethyl-β-cyclodextrin aqueous solution is 2-5 wt %.
[0048] Preferably, the mass ratio of the carboxymethyl-β-cyclodextrin, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt and N-hydroxysuccinimide is 1:(0.8-1):(0.5-0.7), preferably 1:0.9:0.6.
[0049] Preferably, the standing time in step S1 is 2-3 hours.
[0050] Preferably, the mass ratio of the aminated hollow glass microspheres to carboxymethyl-β-cyclodextrin is 1:(3-5).
[0051] Preferably, the temperature of the amidation reaction in step S2 is 25-30° C., and the time of the amidation reaction is 8-12 h.
[0052] Preferably, the preparation method of the aminated hollow glass microspheres is: dispersing the hollow glass microspheres in water, adding polyethyleneimine and epichlorohydrin, and stirring to react, and after the stirring reaction is completed, filtering, washing, and drying the reaction product to obtain the aminated hollow glass microspheres.
[0053] Preferably, the particle size of the hollow glass microspheres is 50-70 μm, preferably 65 μm.
[0054] Further preferably, the preparation method of the aminated hollow glass microspheres is: dispersing the hollow glass microspheres in water, adding polyethyleneimine and epichlorohydrin, stirring and reacting at 70-80° C. for 2-4 hours, and filtering, washing and drying the reaction product after the stirring reaction to obtain the aminated hollow glass microspheres.
[0055] Preferably, the mass ratio of the hollow glass microspheres, water, polyethyleneimine and epichlorohydrin is 1:(20-30):(0.5-0.8):(0.3-0.5), preferably 1:28:0.6:0.4.
[0056] Preferably, the light stabilizer is a liquid hindered amine light stabilizer containing an amino ether group.
[0057] Preferably, the mass ratio of the light stabilizer to methanol is (2-5):100.
[0058] Preferably, the mass ratio of the β-cyclodextrin, the light stabilizer and the water in the loaded hollow glass microspheres is 1:(1.1-1.4):(20-30), preferably 1:1.2:25.
[0059] Preferably, the stirring reaction temperature in step S4 is 25-30° C., and the stirring reaction time is 8-12 h.
[0060] Preferably, the drying agent is a mixture of cerium 2-ethylhexanoate and zirconium 2-ethylhexanoate, and the mass ratio of cerium 2-ethylhexanoate to zirconium 2-ethylhexanoate is (1-3):(1-3), preferably 1:1.
[0061] The second aspect of the present invention provides a method for preparing the above-mentioned high-flash-point phenolic anti-corrosion coating, comprising the following steps: mixing xylene phenolic resin, hyperbranched polyester modified phenolic resin, modified glass fiber, pigment, light stabilizer-β-cyclodextrin inclusion complex and solvent, stirring, adding silicone acrylic emulsion, mixing evenly, and continuing to stir to obtain the high-flash-point phenolic anti-corrosion coating.
[0062] Preferably, the preparation method of the high flash point phenolic anti-corrosion coating comprises the following steps: mixing xylene phenolic resin, hyperbranched polyester modified phenolic resin, modified glass fiber, pigment, light stabilizer-β-cyclodextrin inclusion complex and solvent, stirring at 3000-4000r / min for 30-40min, adding silicone acrylic emulsion, mixing evenly, and continuing to stir at 3000-4000r / min for 30-40min to obtain the high flash point phenolic anti-corrosion coating.
[0063] The third aspect of the present invention provides the use of the above-mentioned high flash point phenolic anti-corrosion coating in the field of outdoor metal substrate protection.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] 1. The present invention creatively prepares a hyperbranched polyester modified phenolic resin, and compounding the hyperbranched polyester modified phenolic resin with a xylene phenolic resin not only improves the adhesion and flexibility of the coating, but also improves the salt spray resistance and weather resistance.
[0066] 2. The present invention creatively prepares modified glass fiber, which not only improves the moisture and heat resistance of the coating, but also improves the salt spray resistance and flexibility.
[0067] 3. The present invention uses 3-[3-carboxyallylamide]propyltriethoxysilane to carboxylate the glass fiber, and the coating has excellent moisture and heat resistance, salt spray resistance and flexibility.
[0068] 4. The present invention creatively prepares a light stabilizer-β-cyclodextrin inclusion complex, which not only improves the weather resistance of the coating, but also further improves the moisture and heat resistance and salt spray resistance. DETAILED DESCRIPTION
[0069] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.
[0070] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0071] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.
[0072] Example 1
[0073] A high-flash-point phenolic anti-corrosion coating, comprising, by weight, 40 parts of xylene phenolic resin, 30 parts of hyperbranched polyester modified phenolic resin, 10 parts of silicone-acrylic emulsion, 5 parts of modified glass fiber, 5 parts of pigment, 3 parts of solvent, 3 parts of light stabilizer-β-cyclodextrin inclusion compound and 1 part of drying agent.
[0074] The xylene phenolic resin is composed of raw materials, by mass, of 20 parts of first formaldehyde, 10 parts of sulfuric acid, 25 parts of xylene, 10 parts of phenol, 0.1 parts of hydrochloric acid, 1 part of sodium hydroxide, 12 parts of second formaldehyde, and 20 parts of ethanol.
[0075] The preparation method of the xylene phenolic resin is as follows: first, formaldehyde and sulfuric acid are mixed uniformly, xylene is added, reacted at 70°C for 8 hours, allowed to stand for 15 minutes, the lower layer solution is removed, washed with water until neutral, the product is vacuumed until no detached matter is present, cooled to 25°C, phenol is added, when the temperature reaches 40°C, hydrochloric acid is added, the temperature is raised to 93°C, reacted for 15 minutes, reacted at 95°C for another 20 minutes, quickly cooled to 40°C, sodium hydroxide is added, reacted for 10 minutes, a second formaldehyde is added, the temperature is raised to 90°C, reacted for 35 minutes, dehydrated at 75°C, cooled to 60°C, ethanol is added to adjust the solid content to 80%, and the xylene phenolic resin is obtained.
[0076] The preparation method of the hyperbranched polyester modified phenolic resin is as follows: formaldehyde, phenol, terminal hydroxyl hyperbranched polyester and water are mixed evenly, sodium hydroxide is added to carry out a first reaction at 85° C. for 3 hours to obtain an intermediate; nano titanium dioxide is added to the intermediate to carry out a second reaction at 70° C. for 6 hours, dehydration is carried out after the reaction is completed, ethanol is added to make the solid content of the hyperbranched polyester modified phenolic resin be 70%, and the mixture is mixed evenly to obtain the hyperbranched polyester modified phenolic resin.
[0077] The terminal hydroxyl hyperbranched polyester is an aliphatic hyperbranched polyester purchased from Wuhan Hyperbranched Resin Technology Co., Ltd., model: H102.
[0078] The mass ratio of the formaldehyde, phenol, terminal hydroxyl hyperbranched polyester and water is 0.45:1:0.1:3.1.
[0079] The mass ratio of the sodium hydroxide to the phenol is 3:100.
[0080] The mass ratio of the intermediate to nano titanium dioxide is 1:0.2.
[0081] The nano titanium dioxide is anatase nano titanium dioxide with a particle size of 20 nm, purchased from Xuancheng Jingrui New Materials Co., Ltd., model: VK-TA18.
[0082] The solid content of the silicone acrylic emulsion is 48±1 wt %, purchased from Jiangsu Shengda New Material Technology Co., Ltd., model: SD-5281 nano silicone acrylic emulsion.
[0083] The preparation method of the modified glass fiber is as follows: carboxylated glass fiber, amino hexagonal boron nitride, epichlorohydrin (CAS No.: 106-89-8) and water are mixed evenly, and a hydrothermal reaction is carried out at 100° C. for 3 hours. After the hydrothermal reaction is completed, the reaction product is filtered, washed and dried in sequence to obtain an intermediate product; the intermediate product is dispersed in an ethanol aqueous solution, and tetraethyl orthosilicate (CAS No.: 78-10-4) and ammonia water are added, and a stirring reaction is carried out at 25° C. for 2.5 hours. After the stirring reaction is completed, the reaction product is filtered, washed and dried in sequence to obtain the modified glass fiber.
[0084] The mass ratio of the carboxylated glass fiber, aminoated hexagonal boron nitride, epichlorohydrin and water is 1:0.7:0.4:50.
[0085] The mass ratio of the intermediate product, ethanol aqueous solution, tetraethyl orthosilicate and ammonia water is 1:25:0.8:1.
[0086] The concentration of the ethanol aqueous solution is 70 wt %.
[0087] The preparation method of the carboxylated glass fiber is as follows: glass fiber, 3-[3-carboxyallylamide]propyltriethoxysilane (CAS No.: 50488-14-7) and ethanol are mixed, and stirred for reaction at 25° C. for 5 hours. After the stirring reaction is completed, the product is filtered, washed and dried to obtain the carboxylated glass fiber.
[0088] The mass ratio of the glass fiber, 3-[3-carboxyallylamide]propyltriethoxysilane and ethanol is 1:0.5:12.
[0089] The glass fiber is glass fiber powder purchased from Taian Zhongshuo Glass Fiber Products Co., Ltd., model: EMG-35.
[0090] The preparation method of the amino-modified hexagonal boron nitride is as follows: dispersing hexagonal boron nitride in water, adding polyethyleneimine (CAS No.: 9002-98-6) and epichlorohydrin, stirring and reacting at 75° C. for 3 hours, filtering, washing and drying the reaction product after the stirring reaction is completed, and obtaining amino-modified hexagonal boron nitride.
[0091] The hexagonal boron nitride was purchased from Henan Boron Nitride New Material Technology Co., Ltd., model: PBN100.
[0092] The mass ratio of the hexagonal boron nitride, water, polyethyleneimine and epichlorohydrin is 1.5:40:1:0.8.
[0093] The pigment is titanium dioxide, purchased from China National Nuclear Huayuan Titanium Dioxide Co., Ltd., model: R-2219.
[0094] The solvent is carbon tetrachloride (CAS No.: 56-23-5).
[0095] The preparation method of the light stabilizer-β-cyclodextrin inclusion compound is as follows:
[0096] S1. Mix carboxymethyl-β-cyclodextrin aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt (CAS No.: 1892-57-5), and N-hydroxysuccinimide (CAS No.: 6066-82-6) evenly, and let stand for 3 hours to obtain an activated carboxymethyl-β-cyclodextrin aqueous solution;
[0097] S2, mixing the activated carboxymethyl-β-cyclodextrin aqueous solution and the aminated hollow glass microspheres, and performing an amidation reaction at 25° C. for 10 h. After the amidation reaction, centrifuging, filtering, and drying the product to obtain β-cyclodextrin loaded with hollow glass microspheres;
[0098] S3, mixing the light stabilizer and methanol to obtain a light stabilizer solution;
[0099] S4. Mix the β-cyclodextrin loaded with hollow glass microspheres, the light stabilizer solution and water, and carry out stirring reaction at 25° C. for 10 hours. After the stirring reaction, centrifuge the product, filter and dry it to obtain a light stabilizer-β-cyclodextrin inclusion complex.
[0100] The concentration of carboxymethyl-β-cyclodextrin in the carboxymethyl-β-cyclodextrin aqueous solution is 3 wt %.
[0101] The carboxymethyl-β-cyclodextrin was purchased from Hubei Xinhongli Chemical Co., Ltd., item number: LI3330.
[0102] The mass ratio of the carboxymethyl-β-cyclodextrin, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt and N-hydroxysuccinimide is 1:0.9:0.6.
[0103] The mass ratio of the aminated hollow glass microspheres to carboxymethyl-β-cyclodextrin is 1:4.
[0104] The preparation method of the aminated hollow glass microspheres is as follows: the hollow glass microspheres are dispersed in water, polyethyleneimine and epichlorohydrin are added, and the reaction is stirred at 75° C. for 3 hours. After the stirring reaction is completed, the reaction product is filtered, washed, and dried to obtain the aminated hollow glass microspheres.
[0105] The hollow glass microspheres have a particle size of 65 μm and are purchased from Wenzhou Weizhen New Materials Co., Ltd., model: 7015.
[0106] The mass ratio of the hollow glass microspheres, water, polyethyleneimine and epichlorohydrin is 1:28:0.6:0.4.
[0107] The light stabilizer is a liquid hindered amine light stabilizer containing an amino ether group, and its trade name is TINUVIN 123 BASF ultraviolet light stabilizer.
[0108] The mass ratio of the light stabilizer to methanol is 4:100.
[0109] The mass ratio of the β-cyclodextrin, the light stabilizer and the water in the loaded hollow glass microspheres is 1:1.2:25.
[0110] The drying agent is a mixture of cerium 2-ethylhexanoate (CAS No.: 56797-01-4) and zirconium 2-ethylhexanoate (CAS No.: 2233-42-3), and the mass ratio of the cerium 2-ethylhexanoate to the zirconium 2-ethylhexanoate is 1:1.
[0111] The preparation method of the above-mentioned high flash point phenolic anti-corrosion coating is: mix xylene phenolic resin, hyperbranched polyester modified phenolic resin, modified glass fiber, pigment, light stabilizer-β-cyclodextrin inclusion complex and solvent, stir for 40 minutes at 4000r / min, add silicone acrylic emulsion, mix evenly, and continue stirring for 30 minutes at 4000r / min to obtain the high flash point phenolic anti-corrosion coating.
[0112] Example 2
[0113] The difference from Example 1 is that the high flash point phenolic anti-corrosion coating, calculated by mass, consists of 70 parts of xylene phenolic resin, 60 parts of hyperbranched polyester modified phenolic resin, 15 parts of silicone acrylic emulsion, 10 parts of modified glass fiber, 10 parts of pigment, 8 parts of solvent, 8 parts of light stabilizer-β-cyclodextrin inclusion complex, and 3 parts of drying agent; the rest are the same.
[0114] The preparation method of the above-mentioned high flash point phenolic anti-corrosion coating is the same as that in Example 1.
[0115] Example 3
[0116] The difference from Example 1 is that the high flash point phenolic anti-corrosion coating is composed of 60 parts of xylene phenolic resin, 45 parts of hyperbranched polyester modified phenolic resin, 12 parts of silicone acrylic emulsion, 8 parts of modified glass fiber, 8 parts of pigment, 6 parts of solvent, 6 parts of light stabilizer-β-cyclodextrin inclusion complex, and 2 parts of drying agent, calculated by mass; the rest are the same.
[0117] The preparation method of the above-mentioned high flash point phenolic anti-corrosion coating is the same as that in Example 1.
[0118] Comparative Example 1
[0119] The difference from Example 3 is that the hyperbranched polyester-modified phenolic resin is replaced by an equal mass of hyperbranched polysilane-modified phenolic resin, and the hyperbranched polysilane-modified phenolic resin is prepared by the preparation method of Example 2 disclosed in Chinese Patent Publication No. CN 116948120A; the rest are the same.
[0120] Comparative Example 2
[0121] The difference from Example 3 is that the preparation method of the hyperbranched polyester modified phenolic resin is: formaldehyde, phenol, terminal hydroxyl hyperbranched polyester and water are uniformly mixed, and sodium hydroxide is added for a first reaction to obtain the hyperbranched polyester modified phenolic resin; the rest are the same.
[0122] Comparative Example 3
[0123] The difference from Example 3 is that the amino-treated hexagonal boron nitride is replaced with amino-treated glass microspheres of the same mass; the rest are the same.
[0124] Comparative Example 4
[0125] The difference from Example 3 is that the preparation method of the carboxylated glass fiber is: adding the glass fiber to a mixed acid of concentrated sulfuric acid and nitric acid, stirring the reaction at 110°C for 3 hours, and after the reaction is completed, centrifuging, washing, and drying to obtain the carboxylated glass fiber; the ratio of the glass fiber, concentrated sulfuric acid, and nitric acid is 1g:12mL:4mL; the rest are the same.
[0126] Comparative Example 5
[0127] The difference from Example 3 is that the aminated hollow glass microspheres are replaced with aminated hexagonal boron nitride of the same mass; the rest are the same.
[0128] Comparative Example 6
[0129] The difference from Example 3 is that the preparation method of the light stabilizer-β-cyclodextrin inclusion complex is:
[0130] S1, mixing carboxymethyl-β-cyclodextrin aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt, and N-hydroxysuccinimide evenly, and letting stand to obtain an activated carboxymethyl-β-cyclodextrin aqueous solution;
[0131] S2, mixing the light stabilizer and methanol to obtain a light stabilizer solution;
[0132] S3. Mix the activated carboxymethyl-β-cyclodextrin aqueous solution and the light stabilizer solution, and stir to react. After the stirring reaction, centrifuge the product, filter, and dry to obtain a light stabilizer-β-cyclodextrin inclusion complex; the mass ratio of the carboxymethyl-β-cyclodextrin to the light stabilizer is 1:1.2; and the rest are the same.
[0133] Comparative Example 7
[0134] The anti-corrosion coating prepared in Example 3 disclosed in Chinese patent publication number CN 113861795 A.
[0135] Test Example 1
[0136] The flash points of the anticorrosive coatings of Examples 1-3 and Comparative Examples 1-7 were tested using GB / T 5208-2008 standard, and the results were all greater than 61°C.
[0137] Test Example 2
[0138] The anticorrosive coatings of Examples 1-3 and Comparative Examples 1-7 were respectively applied to the surface of the tinplate, with a coating thickness of 300 μm, and the following performance tests were performed:
[0139] ① Adhesion: refer to GB / T5210-2006 standard;
[0140] ② Drying time: refer to GB / T1728-1979 standard;
[0141] ③Flexibility: refer to GB / T 1731-2020 standard;
[0142] ④ Salt spray resistance: Refer to GB / T 10125-2021 standard, neutral salt spray test, time: if there is no cracking, blistering or peeling within 2 months (1440h), it is qualified, otherwise it is unqualified;
[0143] ⑤ Weather resistance: Refer to GB / T 23987-2009 standard, use type II lamp, use method B for exposure, if there is no cracking, shedding, powdering or blistering within 1 month (720h), it is qualified, otherwise it is unqualified;
[0144] ⑥Moisture and heat resistance: Refer to GB / T1740-2007 standard. If there is no blistering, cracking or falling off within 1 month (720h), it is considered qualified, otherwise it is considered unqualified.
[0145] The test results are shown in Table 1.
[0146] Table 1 Test results of anticorrosive coatings of Examples 1-3 and Comparative Examples 1-7
[0147]
[0148] As can be seen from Table 1, the coatings obtained from the anticorrosive coatings of Examples 1-3 have good adhesion, flexibility, long-term salt spray resistance, weather resistance, and moisture and heat resistance;
[0149] In Comparative Example 1, since the hyperbranched polyester-modified phenolic resin was replaced with a hyperbranched polysilane-modified phenolic resin of equal mass, the adhesion and flexibility of the obtained coating decreased, and the long-term tests of salt spray resistance and weather resistance failed;
[0150] In Comparative Example 2, since titanium dioxide was not grafted into the hyperbranched polyester-modified phenolic resin, the flexibility of the obtained coating decreased, and the long-term tests of salt spray resistance and weather resistance failed;
[0151] In Comparative Example 3, since the amino-treated hexagonal boron nitride was replaced with amino-treated glass microbeads of equal mass, the flexibility of the obtained coating decreased, and the long-term tests of salt spray resistance and moisture and heat resistance failed;
[0152] Comparative Example 4 Due to the change in the preparation method of the carboxylated glass fiber, the flexibility of the obtained coating decreased, and the long-term tests of salt spray resistance and moisture and heat resistance failed;
[0153] In Comparative Example 5, since the aminated hollow glass microspheres were replaced with aminated hexagonal boron nitride of the same mass, the flexibility of the obtained coating decreased, and the long-term tests of salt spray resistance, weather resistance and heat and humidity resistance failed;
[0154] In Comparative Example 6, since carboxymethyl-β-cyclodextrin was not modified by aminated hollow glass microspheres, the obtained coating failed the long-term tests of salt spray resistance, weather resistance and heat and humidity resistance, and the flexibility was also reduced;
[0155] The anti-corrosion coating of the technical solution disclosed in Comparative Example 7 failed the long-term tests on salt spray resistance, weather resistance and moisture and heat resistance.
[0156] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A high flash point phenolic anticorrosive coating, characterized in that: The raw materials include, by weight: 40-70 parts of xylene phenolic resin, 30-60 parts of hyperbranched polyester modified phenolic resin, 10-15 parts of silicone acrylic emulsion, 5-10 parts of modified glass fiber, 5-10 parts of pigment, 3-8 parts of solvent, 3-8 parts of light stabilizer-β-cyclodextrin inclusion compound, and 1-3 parts of drying agent; The preparation method of the hyperbranched polyester modified phenolic resin comprises the following steps: uniformly mixing formaldehyde, phenol, terminal hydroxyl hyperbranched polyester and water, adding sodium hydroxide for a first reaction to obtain an intermediate; adding nano titanium dioxide to the intermediate for a second reaction, dehydrating after the reaction, adding ethanol and mixing uniformly to obtain the hyperbranched polyester modified phenolic resin.
2. The high flash point phenolic anticorrosive coating according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises the following steps: uniformly mixing carboxylated glass fiber, amino hexagonal boron nitride, epichlorohydrin and water, carrying out hydrothermal reaction, filtering, washing and drying the reaction product in sequence after the hydrothermal reaction is completed to obtain an intermediate product; dispersing the intermediate product in an ethanol aqueous solution, adding tetraethyl orthosilicate and ammonia water to carry out stirring reaction, filtering, washing and drying the reaction product in sequence after the stirring reaction is completed to obtain the modified glass fiber.
3. The high flash point phenolic anticorrosive coating according to claim 2, characterized in that: The mass ratio of the carboxylated glass fiber, amino hexagonal boron nitride, epichlorohydrin and water is 1: (0.5-0.8): (0.3-0.5): (40-60); the mass ratio of the intermediate product, ethanol aqueous solution, tetraethyl orthosilicate and ammonia water is 1: (30-40): (0.7-0.9): (0.9-1.1).
4. The high flash point phenolic anticorrosive coating according to claim 3, characterized in that: The preparation method of the carboxylated glass fiber comprises: mixing glass fiber, 3-[3-carboxyallylamide]propyltriethoxysilane and ethanol, and performing stirring reaction; after the stirring reaction is completed, filtering, washing and drying the product to obtain the carboxylated glass fiber.
5. The high flash point phenolic anticorrosive coating according to claim 4, characterized in that: The preparation method of the amino-modified hexagonal boron nitride comprises: dispersing hexagonal boron nitride in water, adding polyethyleneimine and epichlorohydrin, and stirring to react, and filtering, washing, and drying the reaction product after the stirring reaction is completed to obtain amino-modified hexagonal boron nitride.
6. The high flash point phenolic anticorrosive coating according to claim 1, characterized in that: The preparation method of the light stabilizer-β-cyclodextrin inclusion compound comprises the following steps: S1, mixing carboxymethyl-β-cyclodextrin aqueous solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt, and N-hydroxysuccinimide evenly, and letting stand to obtain an activated carboxymethyl-β-cyclodextrin aqueous solution; S2, mixing the activated carboxymethyl-β-cyclodextrin aqueous solution and the aminated hollow glass microspheres, and performing an amidation reaction. After the amidation reaction, centrifuging, filtering, and drying the product to obtain β-cyclodextrin loaded with hollow glass microspheres; S3, mixing the light stabilizer and methanol to obtain a light stabilizer solution; S4, mixing the β-cyclodextrin loaded with hollow glass microspheres, the light stabilizer solution and water, and stirring the mixture for reaction. After the stirring reaction, centrifuging, filtering and drying the product to obtain a light stabilizer-β-cyclodextrin inclusion complex.
7. The high flash point phenolic anticorrosive coating according to claim 6, characterized in that: The preparation method of the aminated hollow glass microspheres is as follows: the hollow glass microspheres are dispersed in water, polyethyleneimine and epichlorohydrin are added, and the reaction is stirred, and after the stirring reaction is completed, the reaction product is filtered, washed, and dried to obtain the aminated hollow glass microspheres.
8. The high flash point phenolic anticorrosive coating according to claim 7, characterized in that: The light stabilizer is a liquid hindered amine light stabilizer containing an amino ether group.
9. The method for preparing the high flash point phenolic anticorrosive coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mix xylene phenolic resin, hyperbranched polyester modified phenolic resin, modified glass fiber, pigment, light stabilizer-β-cyclodextrin inclusion compound and solvent, stir, add silicone acrylic emulsion, mix evenly, continue stirring to obtain high flash point phenolic anticorrosive coating.
10. Application of the high flash point phenolic anticorrosive coating according to any one of claims 1 to 8 in the field of outdoor metal substrate protection.
Citation Information
Patent Citations
Anticorrosive coating comprising modified phenolic resin
CN112980230A
Preparation method of hyperbranched polysilane modified phenolic resin
CN116948120A
Preparation method of hydrophilic crosslinked polymer hollow microsphere of beta-cyclodextrin
CN102850495A
Anticorrosive oil-resistant paint
CN104403487A
Environment-friendly high-flash-point phenolic aldehyde anticorrosive paint and preparation process thereof
CN113861795A
Cited By
Weather-resistant polysiloxane silicone rubber glass decorative protective coating and preparation method thereof
CN121293876A